Travelling in master class : a look at self-reflection for educators through the medium of a blog - Burnie, Shauna (My University, 2020)
Today, reflection has become a standard element of teacher education programs with the intent of helping teacher candidates demonstrate and build on their understanding of theoretical background and the practical approaches to classroom action (Beauchamp, 2015). After conducting a literature review on the benefit of self-reflection for educators, included in Chapter 2 of my portfolio, it was noted that there is a need for more research to understand the conditions and contexts necessary for educator transformation to take place in the context of classrooms (Arshavskaya, 2017; Beauchamp, 2015), especially with the advent of online tools that promote reflection and communication. Most studies do not directly address the potential blogging has for self-reflection, instead examining this tool for its potential for assessing achievement of learning goals, as well as other activities and assessments (Pascarella, 2009). Beauchamp (2015) specifically argued for a more comprehensive definition of what reflection is in order for educators to gain a better understanding
Keywords: Blogging in teacher education; Criticisms of blogging; Educator self-reflection; Teacher blogs